Hvad gør de med faglighed og køn? - interview med studerende på et humanistisk studium - Knudsen, Susanne V. (Kvinder, Køn & Forskning, 2000)
The article interprets professianlism and gender in mothertongue studies in higher education and research. The interpretation is based on a close reading of interviews with students who are in their second year. Opinions on academic content and approach divide the students, who are writing their M.A. theses, into two groups: some students’ pronouncements are accepting and general, while others are critical and specific in what they say. The opinions on teaching and research devide the students, who are on their second year, where few want more research in their learning, whereas most of the studens are unaware of research in the teaching. They prefer to learn to teach as proffessionals outside the university. Some of the women can tell how their choises to teach outside the university are despised in mothertongue studies in higher education. Theoretically and methodologically the author of this article is inspired by social constructivists and thinking beyond binarities by poststructuralism and postfeminist theories.